Analisis Korelasi Pearson Dalam Menentukan Hubungan Antara Respon Dengan Kepuasan Mahasiswa Menggunakan Aplikasi Quizizz - Jabnabillah, Faradiba; Siska Dwi Astiati (Pi: Mathematics Education Journal, 2024)
The aim of this research is to describe the relationship between response and satisfaction using the Quizizz application as a medium for taking quizzes in calculus courses. The subjects in this research were students of the Information Systems study program semester I in the 2022/2023 academic year who took Calculus courses at the Batam Institute of Technology, totaling 59 people. This research uses the Product Moment correlation test to see whether or not there is a relationship between response (X) and student satisfaction (Y) in using the Quizizz application in the Calculus course. The results of this research are a significant value for the response and satisfaction variables, namely 0.000, where this value is <0.05, thus the response and satisfaction variables have a relationship or correlation. Apart from that, the Pearson Correlation value for response and satisfaction is 0.955, which means that the degree of relationship between these two variables is very strongly correlated and the form of relationship between these two variables is positive, which means that the higher the response, the higher the student satisfaction in using the Quizizz application on the Calculus subject.